0674 Intracerebral Sources of Periodic Leg Movement during Sleep. (27th April 2018) - Kim, T; Cha, K; Jun, J; Lim, J; Byun, J; Sunwoo, J; Shin, J; Han, S; Joo, E; Jung, K
Abstract: Introduction: Periodic leg movements during sleep (PLMS) are repetitive and involuntary jerking movements of the legs during sleep. PLMS are observed in many patients with sleep disorders including restless legs syndrome (RLS). Decreased dopamine transmission associated with neuronal hyper-excitability of the central pattern generator has been suggested as the pathophysiology of PLMS. However, its localization and the origin of rhythmicity remains uncertain. Here, we investigated the intracerebral sources of PLMS using electroencephalographic (EEG) spectral power analysis, and for the first time showed the correlation between rhythmicity of PLMS and intracerebral source. Methods: Polysomnography data of 14 patients with RLS were included in the present study. Electromyographic, 19-channel EEG with 10–20 system, and electrocardiographic (ECG) signals were obtained. To investigate PLMS-related neural synchronies, delta-band (2–4 Hz) and alpha-band (8–12 Hz) activities were analyzed. Spectral power for EEG channels was obtained and topography or average values were measured. The data were analyzed compared to the values of baseline interval which was set to -15 to -10 seconds preceding to the leg movement (LM) onset. Source localization was done using the head model in FreeSurfer toolbox and Beamformer method to solve inverse problems. Correlation between PLMS rhythmicity (PLMS index or inter-movement interval (IMI)) and intracerebral sources were tested. Results: EEG and ECG signals began to change at 3–4 second ahead of LM onset. Especially, delta-band was the first signal to increase, and was immediately followed by ECG and alpha-band signals. Before the LM onset, the source of delta-band was localized into right precentral gyrus between -3 and -2 second. Just after LM onset, the source was at bilateral superior frontal gyri. During -5 and -2 seconds, PLMS index was correlated with delta power in left anterior cingulate gyrus, and IMI was negatively correlated with both left anterior cingulate gyrus and right inferior parietal gyrus. Conclusion: Intracerebral sources of PLMS differed temporally according to the EEG signals. Rhythmicity of PLMS was well correlated with electrophysiological spectral power in cingulate gyrus. Our data provide insight into a cortical organizing mechanism of PLMS. Support (If Any): None.